Understanding the electrochemical reactivity of bamboo multiwalled carbon nanotubes: the presence of oxygenated species at tube ends may not increase electron transfer kinetics - Banks, C; Ji, X; Crossley, A; Compton, R (2006)
The result of acid washing multiwalled carbon bamboo nanotubes is explored with voltammetry and X-ray Photoelectron Spectroscopy; it is found that the presence of oxygenated species formed as a result at the ends of the nanotubes does not measurably change the heterogeneous charge transfer kinetics. © 2006 Wiley-VCH Verlag GmbH and Co. KGaA.